Papers - - Production Engineering - Investigations on the Recovery of Oil from Sandstones by Gas Drive - Gerald L. Hassler; Raymond R. Rice; Erwin H. Leeman (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1936)
In the past few years a great deal of preeise information has been obtained about the relation of natural gas to oil production1. The improvement of our understanding has been of great value, both in prolonging the life of wells and in providing a much needed technical background for the legal problem of proration. But there are two principal aspects of the problem of production. It is necessary to consider not only the energy available, in the form of compressed and dissolved gas and in the pressure of driving water, but also the tenacity with which the sandstone holds the oil. The amount of oil that each sand condition will produce under given conditions of gas content should be determined. Hitherto the effect of the sand has been judged by a study of the flow of each well coupled with a procedure for extrapolating the production curve; hut, as is well known to evaluation engineers, such production curves are subject to changes that are not well understood, and often are affected by outside disturbances. On the whole, the concept of "potential production" is vague principally because the influence of the sand in production is not known beyond the simple ideas of porosity and permeability. The permeability is a quantity that has only inference value where mixtures of gas and oil or of gas, oil and water are present. Excellent studies of the production of oil from reservoirs packed with unconsolidatcd sand are available2, but these studies treat largely of small-scale analogzes to a producing field, and the conclusions to be derived from them arc necessarily of a qualitative character because it is not known in what way these miniature oil fields resemble large ones.